2009
DOI: 10.1117/12.825614
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of high concentration flat-plate Fresnel lenses

Abstract: In the work, stages of designing, optimizing, manufacturing and testing the circular flat-plate Fresnel lenses (FLs) for photovoltaic modules with multi-junction solar cells (SCs) are presented. A mathematical model based on ray tracing has been developed for optimizing lenses design parameters and calculating their optical-power characteristics (OPCs). In searching the optimum combination of the lens aperture, its focal distance and refracting profile parameters, the optimization criterion was the maximum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of the mathematical simulation of characteristics of circular FLs with flat operating facets show [16] that, to rise their power efficiency, it is necessary to decrease the profile tooth pitches, and, hence, to increase their number at a preset lens size. The positive effect is achieved, in this case, due to more precise approximation of the initial plane-convex lens surface by the great number of sections of the operating facet conical surfaces (facet generating lines are straight ones).…”
Section: Lenses With Improved Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the mathematical simulation of characteristics of circular FLs with flat operating facets show [16] that, to rise their power efficiency, it is necessary to decrease the profile tooth pitches, and, hence, to increase their number at a preset lens size. The positive effect is achieved, in this case, due to more precise approximation of the initial plane-convex lens surface by the great number of sections of the operating facet conical surfaces (facet generating lines are straight ones).…”
Section: Lenses With Improved Characteristicsmentioning
confidence: 99%
“…Investigation of the effect of the profile pitch on the average concentration ratio K av in the focal spot (interception coefficient K int =0.95) of FLs with straight and curved generating lines of operating facets have shown that FLs with curved generating lines of operating facets conserve a relatively high concentrating capability in the whole investigated range of the profile pitch variation [16]. The comparison was carried out for combined "silicon-on-glass" FL with the side dimension…”
Section: Lenses With Improved Characteristicsmentioning
confidence: 99%